Forme urbaine et mobilités de loisirs : l’« effet barbecue » sur le grill - Sébastien Munafò (Cybergeo)
Several studies have underlined so far that the residents of city centers, with similar income levels, tend to travel more during their leisure time than people in more peripheral areas. One hypothesis put forward to explain this phenomenon suggests that suburban residents enjoy a more pleasant environment for recreation (better prone to barbecue parties for instance) while central city dwellers are forced to travel more in order to enjoy nature and quietness. This hypothesis is framed as the “compensation effect” or “barbecue effect”. Due to the very high level of energy consumption of leisure mobilities, this effect would lead to deeply question the virtues of the compact city in terms of sustainable mobility.This article is focused on testing the compensation hypothesis on the cases of Geneva and Zurich. Our quantitative and qualitative data lead us to reject this hypothesis. The occasional mobility of city center inhabitants is actually very important and largely unknown but far from being strictly related to a desire of nature. It also doesn’t fit with any compensation idea. Moreover, its energy impact is not important enough to actually reverse the contrasts of sustainability between compact and suburban forms in terms of mobility.